MORPHOLOGICAL AND MOLECULAR DESCRIPTION OF NEW RECORD OF METARHABDITIS RAINAI (NEMATODA: RHABDITIDAE) FROM BAGHDAD - Kadhim, Zahraa Y.; Al-Warid , Harith S.; Al-Zaidawi, Jawad B. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Aim of this study was to identify and characterize the entomopathogenic nematode Metarhabditis rainai, which was isolated from soil samples carried out from Alrashdya at (33˚25ˈ13.4̎ N 44˚21ˈ45.3̎ E) Baghdad- Iraq and was illustrated by both morphological and molecular aspects.  All specimens of M. rainai were cultured, identified and described using some morphometric criteria based on standard available key. Selected specimens (Zah, IQ2 OR960470 isolate) of this species were characterized by the body length of male was ranged from (377.49 – 563.89 μm), the body length of female was (857.44 – 1111.7 μm) and the body length of juvenile was (419.28 – 757 μm). Using partial 18S rRNA gene sequences, molecular characterization was performed on selected specimens of this species. The 18S-rRNA sequence of the Zah, IQ2 OR960470 isolate showed a sequence homology ranging from (88.50% to 100%) with the 18S rRNA sequence of M. rainai found in the NCBI database. The phylogenetic tree has been created to separate M. rainai species from closely related genera and species. Metarhabditis rainai Zah, IQ2 OR960470 isolate marks the first record of M. rainai in Iraq.